All Days 2012
DOI: 10.2118/155403-ms
|View full text |Cite
|
Sign up to set email alerts
|

Alkali-Surfactant-Polymer Flooding Pilot Test in Southern Oman

Abstract: Petroleum Development Oman is advancing a pattern flood pilot in a major sandstone field in Southern Oman that uses a chemical EOR flooding process to recover additional reserves. An EOR screening study showed that Alkali-Surfactant-Polymer is a viable technology for this viscous oil reservoir (90 cP). A successful ASP pilot test will pave the way to potentially implement the process in other sandstone fields in the Southern Oman Basin. The ASP pilot test is a unique project in which two anionic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Although ASP flooding seems promising in the laboratory as a tertiary recovery method, field experience has revealed several complicating features of the technology. Thus, it has been observed that the main problems while ASP flooding is related to operational arrays [12][13][14][15]. The scaling problem is the most common among ASP flood projects, and it creates the need to redesign surface facilities from ASP solution preparation units to production and processing units.…”
Section: Chemical (Asp) Flood Risks and Feasibility Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Although ASP flooding seems promising in the laboratory as a tertiary recovery method, field experience has revealed several complicating features of the technology. Thus, it has been observed that the main problems while ASP flooding is related to operational arrays [12][13][14][15]. The scaling problem is the most common among ASP flood projects, and it creates the need to redesign surface facilities from ASP solution preparation units to production and processing units.…”
Section: Chemical (Asp) Flood Risks and Feasibility Assessmentmentioning
confidence: 99%
“…Therefore, potential emulsification issues should be envisaged preliminary as it was done in the Bhagyam field having additional demulsifier injection wells near producers [12]. Also, Finol et al [13] have reported preliminary laboratory experiments on identifying cost-effective demulsifiers in the designing stage of the Al Khalata pilot test.…”
Section: Chemical (Asp) Flood Risks and Feasibility Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…ASP or SP is a logical extension and has the promise to liberate the trapped oil. Consequently, there are several pattern-flood pilots in progress or about to be executed to evaluate ASP at a scale relevant to commercial scale application [14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…[1--4] The ASP flooding with water, under favorable conditions, can lead to mobilization of the residual oil and improved displacement efficiency. [5,6] Even though success of the ASP has been mostly demonstrated in laboratory test, ASP flooding is very sensitive to heterogeneities in the reservoir, and it is necessary to have a comprehensive investigation of ASP flooding in reservoirs with different petrophysical properties for a wider and more successful implementation. [4] Surfactant solution tends to decrease the interfacial tension (IFT) between oil and injected fluid, altering the reservoir wettability toward water-wetted one, and improves the sweep efficiency through creating macroemulsions or microemulsions with oil and water.…”
Section: Introductionmentioning
confidence: 99%